아동이 지각한 부모의 양육행동과 또래 괴롭힘에 관한 단기종단연구 : 아동의 성을 중심으로 - 심희옥; Sim, Hee-Og (Korean Journal of child studies, 2010)
This study explored the differences in gender, developmental period and parents in terms of parenting, the cross-sectional and longitudinal relationships in parenting by gender, and the cross-sectional and longitudinal relationships between participant roles in bullying situations and parenting by gender. The subjects were 498 4-5th grade children and the instruments utilized in this study were the Parental Bonding Instrument (Bowers, Smith, & Binney, 1994) and the Participant Roles Scale (Sutton & Smith, 1999). The subjects were contacted again one year after the first contact. Results showed that the relationships between parents were longitudinally quite stable. Girls whose fathers had higher levels of accurate monitoring were more likely to be defenders cross-sectionally. Girls whose parents had more accurate monitoring were less likely to be victims longitudinally. The results underscore the importance of examining both gender and participant roles in bullying situations.